DEVELOPMENT OF LEARNING RESOURCES FOR A COLLECTION OF SHORT STORIES ABOUT THE HISTORY OF THE BUBONIC PLAGUE IN MALANG FOR ELEVEN GRADE STUDENTS - Kholifah, Adin Nur (Universitas Negeri Yogyakarta, 2024)
The purpose of writing this article is to develop and test the feasibility of learning resources for a collection of short stories from the history of the bubonic plague in Malang in 1911-1916. The writing of this article uses the research and development (R&D) method. The R&D model used by researchers is a procedural model. The procedural model itself consists of ten steps: 1) looking at potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) trial usage, 7) product revision, 8) trial product, 9) product revision, 10) mass production. Research and development of Striped Collar learning resources up to step 5, namely product design revision. The result of the development that the researchers did was a product that has the potential to be used as a learning resource by obtaining 91% validity from material experts and 88.5% validity from learning resource experts.